2022
DOI: 10.3390/f13030423
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics and Climate Influence of Forest Fires in Fujian Province, China

Abstract: Climate determines the spatiotemporal distribution pattern of forest fires by affecting vegetation and the extent of drought. Thus, analyzing the dynamic change of the forest fire season and its response to climate change will play an important role in targeted adjustments of forest fire management policies and practices. In this study, we studied the spatiotemporal variations in forest fire occurrence in Fujian Province, China using the Mann–Kendall trend test and correlation analysis to analyze Moderate Reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…It might be worth looking at changes in the occurrence of fires over time and forecasting throughout the year, which we strongly recommend. This conclusion is also supported by the results of fire studies from Fujian province in China in the 2001 to 2016 period [30], where the incidence of forest fires first increased and then decreased over the years, but the percentage of forest fires declined during the fire prevention season. The number of forest fires increased significantly in spring and summer, exceeding the number of forest fires occurring during the 2010 fire prevention period [30].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It might be worth looking at changes in the occurrence of fires over time and forecasting throughout the year, which we strongly recommend. This conclusion is also supported by the results of fire studies from Fujian province in China in the 2001 to 2016 period [30], where the incidence of forest fires first increased and then decreased over the years, but the percentage of forest fires declined during the fire prevention season. The number of forest fires increased significantly in spring and summer, exceeding the number of forest fires occurring during the 2010 fire prevention period [30].…”
Section: Discussionmentioning
confidence: 53%
“…This conclusion is also supported by the results of fire studies from Fujian province in China in the 2001 to 2016 period [30], where the incidence of forest fires first increased and then decreased over the years, but the percentage of forest fires declined during the fire prevention season. The number of forest fires increased significantly in spring and summer, exceeding the number of forest fires occurring during the 2010 fire prevention period [30]. The spatial distribution of forest fires also changed: the number of fires decreased from northwestern to southeastern coastal areas, and the number of forest fires in the northwestern mountainous areas declined rapidly in autumn and winter.…”
Section: Discussionmentioning
confidence: 53%
“…The frequent forest res in recent years are believed to be attributed to the changing climate conditions. In other words, climate determines the spatiotemporal distribution, intensity, and patterns of forest res by affecting vegetation and the extent of drought (Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…[17]. Fires also have an impact on these factors; for example, studies have shown that the occurrence of forest fires changes the distribution of vegetation [18].…”
Section: Introductionmentioning
confidence: 99%